APP Protein Family Signaling at the Synapse: Insights from Intracellular APP-Binding Proteins - Guénette, Suzanne; Strecker, Paul; Kins, Stefan (Frontiers in Molecular Neuroscience, 2017)
Understanding the molecular mechanisms underlying Amyloid Precursor Protein family (APP/APLP) function in the nervous system can be achieved by studying the APP/APLP interactome. In this review, we focused on intracellular APP interacting proteins that bind the YENPTY internalization motif located in the last fifteen amino acids of the C-terminal region. These proteins, which include X11/Mints and FE65/FE65Ls, represent APP cytosolic binding partners exhibiting different neuronal functions. A comparison of FE65 and APP family member mutant mice revealed a shared function for APP/FE65 protein family members in neurogenesis and neuronal positioning. Accumulating evidence also supports a role for membrane-associated APP/APLP proteins in synapse formation and function. Therefore, it is tempting to speculate that APP/APLP C-terminal interacting proteins transmit APP/APLP-dependent signals at the synapse. Herein, we compare our current knowledge of the synaptic phenotypes of APP/APLP mutant mice with those of mice lacking different APP/APLP interaction partners and discuss the possible downstream effects of APP-dependent FE65/FE65L or X11/Mint signaling on synaptic vesicle release, synaptic morphology and function. Given that the role of X11/Mint proteins at the synapse is well-established, we propose a model highlighting the role of FE65 protein family members for transduction of APP/APLP physiological function at the synapse.